2015
DOI: 10.1111/cobi.12634
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms for parasite conservation

Abstract: Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
85
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 57 publications
0
85
0
1
Order By: Relevance
“…The summer−fall decline in D. pristidis populations corresponds with the rainy season in south Florida (June to November), a period during which marked drops in salinity can influence the movements of smalltooth sawfish within the nursery, but they remain within it (Poulakis et al 2011(Poulakis et al , 2013. Parasites have been called ecological puppeteers because their impacts on individual hosts' health and behavior can be profound at the ecosystem (collective) level (Dougherty et al 2016), and the possibility that infection by D. pristidis could influence host movements in the Charlotte Harbor estuarine system is intriguing. Poulakis et al (2011) suggested that the tendency for juvenile smalltooth sawfish to remain in place during periods of high freshwater flow might be an adaptive strategy for avoiding predators and competitors, but they did not consider whether low salinity might have a prophylactic effect on ectoparasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summer−fall decline in D. pristidis populations corresponds with the rainy season in south Florida (June to November), a period during which marked drops in salinity can influence the movements of smalltooth sawfish within the nursery, but they remain within it (Poulakis et al 2011(Poulakis et al , 2013. Parasites have been called ecological puppeteers because their impacts on individual hosts' health and behavior can be profound at the ecosystem (collective) level (Dougherty et al 2016), and the possibility that infection by D. pristidis could influence host movements in the Charlotte Harbor estuarine system is intriguing. Poulakis et al (2011) suggested that the tendency for juvenile smalltooth sawfish to remain in place during periods of high freshwater flow might be an adaptive strategy for avoiding predators and competitors, but they did not consider whether low salinity might have a prophylactic effect on ectoparasites.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to parasites has largely focused on their role as agents of disease, but a full understanding of their complex ecological function requires broader consideration (Wood & Johnson 2015). They are, in fact, an integral component of a healthy ecosystem and can serve as biological indicators of host and environmental health (Marcogliese 2005, Dougherty et al 2016. Some may reduce transmission rates of more pathogenic species (Johnson et al 2013), act as contaminant sinks (Sures 2003), indicate host ancestry, or serve as biological tags (Whiteman & Parker 2005).…”
Section: Introductionmentioning
confidence: 99%
“…, Gómez & Nichols , Dougherty et al . ). However, parasite–host interactions are often studied as discrete topics from (or analogs to) predator–prey interactions rather than dynamic parts of an integrated system (Raffel et al .…”
mentioning
confidence: 97%
“…THE ROLE OF PARASITES IN ECOSYSTEMS HAS HISTORICALLY BEEN CONSIDERED TRIVIAL (Marcogliese 2004, Hudson et al 2006, until developments in the past few decades revealed the significant control that parasites have over their hosts' densities and population cycles (Hansson 1987, Hudson et al 1998, Klemola et al 2003, and how they shape community structure (Mouritsen & Poulin 2005, Wood et al 2007, Kuris et al 2008. A growing body of evidence also suggests that ecosystem function and resilience improve with increased parasite diversity (Hudson et al 2006, G omez & Nichols 2013, Dougherty et al 2016). However, parasite-host interactions are often studied as discrete topics from (or analogs to) predator-prey interactions rather than dynamic parts of an integrated system (Raffel et al 2008).…”
mentioning
confidence: 99%
“…In these books, the reader would look in vain for a chapter advocating a paradigm shift in how we consider pests and pathogens, as was recently the case in this journal for animal parasites (Dougherty et al. ). We try to preserve threatened animals and plants, but what about endangered pests and pathogens (Ingram )?…”
mentioning
confidence: 99%